Implementation of renewable energy using smart light solar cell system for mosque energy efficiency - Wahyu Hariyanto; Shoffin Nahwa Utama; Fatchurrohman Fatchurrohman (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
The outreach activity focuses on improving energy efficiency at Sirothol Mustaqim Mosque in Pasuruan Regency. The primary issue addressed is how to meet the lighting needs of the mosque while minimizing the use of PLN electricity and optimizing the use of lamps and electricity based on the number of congregants. The main objective is to implement renewable energy through solar panels to replace conventional electricity, analyze the efficiency of electricity usage based on lighting requirements, and enhance electricity efficiency based on time and lamp location. Expected outcomes include increased electricity usage efficiency, reduced operational costs for mosque management, and advanced scientific and technological knowledge in the general community. The participatory action research (PAR) method emphasizes active participation and collaboration between academics and the community. The project commences with a field survey to identify energy needs and the potential for solar energy sources on-site. Subsequently, project planning and design are carried out, followed by project implementation with training for mosque administrators. The results of the project's implementation include energy usage efficiency, the integration of renewable energy in a religious context, and contributions to understanding environmental responsibilities. The success of the implementation measure calculations for the usage time of 40-watt lamps using solar energy are provided, along with a comparison of PLN electricity costs and solar energy usage costs. The analyses demonstrate favorable energy efficiency using solar power.